Validation of the 30 Second Asthma Test™ as a Measure of Asthma Control - Sara Ahmed; Pierre Ernst; Robyn Tamblyn; Neil Colman (Canadian Respiratory Journal)
BACKGROUND: The primary objective of asthma management is to help patients establish and maintain optimal disease control. Simple and efficient tools are needed to assess patient-reported symptoms so that they can be used with or without airway function to evaluate asthma control.